A COMPARATIVE ANALYSIS OF EQUITY SHARE AND FUTURE & OPTION WITH SPECIAL REFERENCE TO NSE - Chaplot, Himanshu; Jain, Jayshree; Dashora, Devesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Stock or Share people invested for profit. Their profit may vary time to time. Most of the time they were in loss. They were in loss because of volatility in stock market. Most of the investors are short term, mid-term or long-term investors. Investors not only invest in Equity market but also doing Future and Option trading. So, our research mostly compares with Equity market and Future and option trading. The data we collected are secondary data. The Sample data we collected from survey and the size of sample data is 214.The Algorithm we use in our research paper is Machine Learning Algorithm i.e., Regression and Classification Algorithm to compare which is best for future profit and quick money and also, we use various Preprocessing technique to correct sample data.